2009
DOI: 10.1111/j.1551-2916.2009.03343.x
|View full text |Cite
|
Sign up to set email alerts
|

White Luminescence from Sol–Gel‐Derived SiOC Thin Films

Abstract: A new approach to obtain visible luminescence from sol–gel‐derived SiOC films is proposed. In order to investigate the influence of Si and C content, Si‐ and C‐rich SiOC films were prepared as well as stoichiometric SiOC films. High intense white luminescence is obtained where the emission color can be controlled by the experimental parameters such as the starting sol–gel‐composition and the pyrolysis temperature. In stoichiometric SiOC films, low pyrolysis temperature yields UV‐blue luminescence, whereas high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…Karakuscu et al proposed idea of PL centers related to dangling bonds at early stage of ceramization (800-1000 • C) of sol-gel derived Si−O−C films. 6 Menapace et al observed remarkable increase of dangling bonds during precursor pyrolysis up to 700 • C, and assigned them to carbon radicals. 30 In summary, bond cleavage of Si−CH 3 in the precursor and incorporation of sp 3 carbon in amorphous Si−O−C(−H) network is suggested to occur at the temperature range of 750-850 • C. First chemical step of such incorporation would be formation of Si−CH 2 −Si bridges.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%
See 1 more Smart Citation
“…Karakuscu et al proposed idea of PL centers related to dangling bonds at early stage of ceramization (800-1000 • C) of sol-gel derived Si−O−C films. 6 Menapace et al observed remarkable increase of dangling bonds during precursor pyrolysis up to 700 • C, and assigned them to carbon radicals. 30 In summary, bond cleavage of Si−CH 3 in the precursor and incorporation of sp 3 carbon in amorphous Si−O−C(−H) network is suggested to occur at the temperature range of 750-850 • C. First chemical step of such incorporation would be formation of Si−CH 2 −Si bridges.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%
“…Various kinds of Si−O−C ceramics were synthesized by various methods, and many mechanisms have been proposed to explain the observed PL bands. [3][4][5][6][7][8][9] Their simple chemical composition with no special activator was promising for their use in LED systems, devices of radiation detectors or environmental resistant inorganic pigments with fluorescent colors.…”
Section: Author(s) All Article Content Except Where Otherwise Notedmentioning
confidence: 99%
“…With a refractive index that can be tuned between silica glass SiO2 (1.45) and amorphous silicon carbide a-SiC (3.2), silicon oxycarbide SiOC offers this flexibility. However, the methods which were used to produce silicon oxycarbide such as chemical vapor deposition (CVD) [1,2,3,4] and sol-gel pyrolysis [5,6,7,8] introduce hydrogen and high material absorption. In the recent years, the authors in [9,10] showed the deposition of SiOC films with RF sputtering technique and discussed physical and structural characteristics of SiOC thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, for such kind devices SiO 2 -Si structures are used with the oxide doped with rear-earth impurities [3] or enriched with Si nanocrystals [5], which results in colour changing from red to blue in the former case and from red to infra-red in the latter one. Recently, it was demonstrated that silicon oxycarbide by itself can efficiently emit white photo- [6,7] and electroluminescence [8]. On the other hand, embedding rear-earth (RE) metals into silicon oxycarbide resulted in a more significant increase of photoluminescence (PL) intensity at wavelengths corresponding to intra-4f shell transitions of the impurity in comparison with the PL intensity at the same wavelengths for the RE embedded in SiO 2 matrix [9].…”
Section: Introductionmentioning
confidence: 99%